Asymmetric Organocatalysis with Chiral Covalent Organic Frameworks - Yu, Song-Chen; Cheng, Liang; Liu, Li (Organic Materials, 2021)
Inspired by Mother Nature, the use of chiral covalent organic frameworks as heterogeneous asymmetric organocatalysts has arisen over the last decade as a new method in enantioselective synthesis. In this Short Review, sophisticated design of these polymeric materials and their application in asymmetric organocatalysis will be discussed.
Keywords: chiral covalent organic frameworks; post-modification; asymmetric organocatalysis; enantioselective synthesis